2023
DOI: 10.3390/molecules28104170
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Tyrosinase, Xanthine Oxidase, and α-Glucosidase Inhibitors from Polygoni Cuspidati Rhizoma et Radix by Ultrafiltration and HPLC Analysis

Abstract: Polygoni Cuspidati Rhizoma et Radix (PCR), the rhizome and root of Polygonum cuspidatum Sieb. et Zucc., has been used as an herbal medicine for a long time. In this study, the ultrafiltration combined with high performance liquid chromatography (UF-HPLC) method was developed to screen tyrosinase (TYR), α-glucosidase (α-GLU), and xanthine oxidase (XOD) inhibitors from PCR. Firstly, the inhibitory activity of 50% methanol PCR extract on TYR, α-GLU, XOD, and acetylcholinesterase (ACHE) was tested. The extract sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The purified OFI extract showed better inhibitory activity against α-Glu than against acarbose (IC 50 = 345.67 µg/mL), whereas the inhibitory activity against XOD was less potent than that of allopurinol (IC 50 = 12.00 µg/mL). The results showed similar trends to the inhibitory effect of the extract from Polygoni Cuspidati Rhizoma et Radix on α-Glu and XOD (Chen et al, 2023). The extraction yield of polyphenols after OFI purification increased from 4.12% to 35.50%.…”
Section: Tfc Tsc Antioxidant Activities Xod Inhibitory Activity and α...supporting
confidence: 68%
“…The purified OFI extract showed better inhibitory activity against α-Glu than against acarbose (IC 50 = 345.67 µg/mL), whereas the inhibitory activity against XOD was less potent than that of allopurinol (IC 50 = 12.00 µg/mL). The results showed similar trends to the inhibitory effect of the extract from Polygoni Cuspidati Rhizoma et Radix on α-Glu and XOD (Chen et al, 2023). The extraction yield of polyphenols after OFI purification increased from 4.12% to 35.50%.…”
Section: Tfc Tsc Antioxidant Activities Xod Inhibitory Activity and α...supporting
confidence: 68%
“…In the field of antioxidant research, molecular docking analysis has been widely adopted, particularly for exploring how antioxidants interact with specific targets to elicit their functions [33,34]. This approach not only aids in understanding the molecular-level efficacy of antioxidants, but also lays a solid theoretical foundation for online antioxidant screening.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Polygonum cuspidatum (PC) extract has been included in the “Catalog of Used Cosmetic Ingredients (2021 Edition)” and is added to thousands of cosmetic products ( ) (accessed on 25 September 2023). Some studies have shown that PC extracts prepared by different methods have certain TYR inhibitory effects [ 11 , 12 , 13 ]. Although PC extract is widely used in whitening cosmetics, there are no quality standards for its application in cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…bevol.cn/index.html) (accessed on 25 September 2023). Some studies have shown that PC extracts prepared by different methods have certain TYR inhibitory effects [11][12][13]. Although PC extract is widely used in whitening cosmetics, there are no quality standards for its application in cosmetics.…”
Section: Introductionmentioning
confidence: 99%